Konstruksi Otoritas Hadis dalam Tradisi Keilmuan Islam: Relevansi Klasifikasi Sahih, Hasan, dan Daif di Tengah Dialektika Klasik dan Modern - Lyra Laililrizqi; Farah Fauza Finnas; Kasuwi Saeban; Ahmad Manshur (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This article examines the construction of hadith authority within the Islamic scholarly tradition by positioning the classifications of sahih, hasan and da’if as an epistemological foundation for determining the reliability and validity of a narration. This study is motivated by the tendency for discussions of hadith to often stop at normative definitions, meaning that the role of hadith classification as a determinant of the scientific legitimacy of a narration has not yet been examined in depth. This research aims to explain the function of hadith classification as the epistemological basis of hadith authority, assess its relevance in contemporary hadith interpretation, and formulate a conceptual model that can bridge classical authority and the needs of modern interpretation. This research employs a qualitative approach using a literature review of classical and contemporary literature in hadith studies. The findings indicate that classical hadith classification theory retains strong significance in maintaining the discipline of verification, historical credibility, and the scientific validity of hadith. However, these theories have limitations when confronted with issues of socio-historical context, interpretation, and practical relevance in modern life. Therefore, this article proposes an integrative model that combines traditional chain of transmission verification with analysis of the text, historical context, normative objectives, as well as ethical and practical relevance. This model allows the authority of hadith to be preserved epistemologically whilst remaining responsive to the challenges of modernity